Productive Diversification of African Agriculture and Its Effects on Resilience and Nutrition - World Bank (World Bank, Washington, DC, 2018)
The agriculture sector in Sub-Saharan Africa (SSA) remains the backbone of national economies, sustaining rural and urban livelihoods alike, and providing food and income for the majority of households. Recent agriculture growth in Sub-Saharan Africa has been solid and has supported improvements in nutrition outcomes and poverty rates.Despite some relative gains, food insecurity and malnutrition in absolute terms continue to be major public health challenges in most African countries south of the Sahara, and most recent data are cause for concern. Many countries are still highly reliant on the production of one crop for national food security, which largely determines the total caloric intake of the rural population. Farmers in Sub-Saharan African are vulnerable to market risks and weather-related risks and shocks. Decisions on whether to diversify or to specialize production impact resilience, and thus their capacity to cope with and adapt to these risks. Market- and climate-related risks to smallholders in SSA are compounded by predictions that both the suitability of crop area for staples such as maize, and crop nutrient content could be substantially lowered with rising average temperatures. This report highlights that there is no one-size-fits-all solution in fostering diversification and provides a selection of policies available to governments that can promote or constrain diversification.